A new species of Polyonyx (Crustacea, Anomura, Porcellanidae) inhabiting polychaete-worm tubes (Annelida, Chaetopteridae) in the Indo-West Pacific - Werding, Bernd; Hiller, Alexandra; Justus Liebig University Giessen (My University, 2019)
Polyonyx socialis sp. n. from the South China Sea of Vietnam is described. The new species was collected in a previous study that compared the vertebrate and invertebrate symbiont communities living in the tubes of two syntopic species of the polychaete genus Chaetopterus. Polyonyx socialis sp. n. inhabits the tubes of the smaller polychaete species as a heterosexual pair, and frequently shares the cavity of the host s tube with a larger porcellanid, P. heok, also present as a male-female pair, and with a species of trinchesiid nudibranch. Less frequently, the new species shares its host with a heterosexual pair of a larger species of pinnotherid crab. Polyonyx socialis sp. n. belongs to the P. sinensis group, a world-wide distributed morphological line within the heterogeneous genus Polyonyx. Most species in this group are obligate commensals of chaetopterid polychaetes. The crabs have a transversally cylindrical habitus, which enables them to move laterally along the worm tubes with ease. Polyonyx socialis sp. n. is a relatively small species that lives attached to the inner walls of the polychaete tube. The small size and flattened chelipeds and walking legs of the new species confers it an advantage to cohabiting the same worm tube with larger decapod species occupying most of the tube s cavity.
Keywords: adaptation; Chaetopterus; commensalism; polychaete-inhabiting; ddc:590